2009
DOI: 10.1111/j.1532-849x.2009.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness of a Resin Cement Polymerized by Light‐Emitting Diode and Halogen Lights through Ceramic

Abstract: The efficiency of high-power LED light in polymerization of the resin cement used in this study was comparable to the high-power QTH light only with a longer exposure time. A reduced curing time of 20 seconds with high-power LED light for photopolymerizing the dual-cured resin cement under ceramic restorations with a minimum 2-mm thickness is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 24 publications
0
17
1
12
Order By: Relevance
“…There is no internationally recognized standard for adequate depth of cure as measured by the relative hardness method 17 . For proper depth of cure, a relative hardness value (100 x hardness of lower surface/hardness of top surface) must be higher than 80% 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no internationally recognized standard for adequate depth of cure as measured by the relative hardness method 17 . For proper depth of cure, a relative hardness value (100 x hardness of lower surface/hardness of top surface) must be higher than 80% 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that LED is now as effective as QTH curing light units 4,17,28,30 . LED units have an expected lifetime of several thousand h without significant degradation of light flux over time and no filters are required, since their spectral output falls conveniently within the absorption spectrum of the camphoroquinone photoinitiator (400-500 nm) 18,31,34 .…”
Section: Introductionmentioning
confidence: 99%
“…The success of indirect esthetic restorations depends mainly on the luting agent, which should guarantee an effective bonding between the restoration and the dental substrate, preserving the marginal seal (1). Despite the variety of commercially available cements, there is no ideal cement for all clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Vários fatores podem influenciar a polimerização do cimento empregado na cimentação de coroas confeccionadas em cerâmica: a composição, espessura, opacidade e a cor do material cerâmico podem atenuar a passagem da fonte luz e, consequentemente, diminuir a porcentagem de polimerização do cimento (BLACKMAN; BARGHI; DUKE, 1990, EL-MOWAFY;RUBO, 2000, SOARES;SILVA;FONSECA, 2006YOSHIDA;ATSUTA, 2008, ILIE;HICKEL, 2008, PAZIN et al, 2008MAHMOOD;KESHVAD, 2009, NORONHA-FILHO et al, 2010, VALENTINO et al, 2010. As características dos substratos e do agente cimentante também são fatores determinantes do resultado final da restauração (CARVALHO et al, 2004a, CEBALLOS et al, 2007, MANSO et al, 2011.…”
Section: Introdução 19unclassified